Geochemistry of the Late Cretaceous Pandan Formation in Cebu Island, Central Philippines: Sediment contributions from the Australian plate margin during the Mesozoic. (16th March 2020) - Rodrigo, Jerali D.; Gabo‐Ratio, Jillian Aira S.; Queaño, Karlo L.; Fernando, Allan Gil S.; de Silva, Leopoldo P.; Yonezu, Kotaro; Zhang, Yu
Abstract: The Late Cretaceous Pandan Formation in Cebu Island is one of the oldest sedimentary units in the Central Philippines. The inconsistencies in geological descriptions and interpretation of the depositional environment of the Pandan Formation complicated efforts to determine the origin and tectonic history of the basement of Cebu Island. This study therefore looks into the petrological and geochemical characteristics of the Pandan Formation and their implications for the tectonic development of the Philippine Arc during the late Mesozoic. Petrographic analyses indicate significant contribution from mafic sources with additional inputs from felsic rocks, siliciclastics and metamorphic sources. Enrichment of detrital quartz from felsic volcanic and plutonic rocks, as well as from siliciclastic and metamorphic sources, has shifted the SiO2 composition of the Pandan clastics from a mafic to a more intermediate source. Whole‐rock geochemical analyses revealed low SiO2 /Al2 O3  = 4.21, low K2 O/Na2 O = 1.16,  low Th/Sc = 0.13,  low Th/U = 2.78,  high La/Th = 4.51, significantly low REEs =  ca  76.45 ppm and low LaN /YbN  = 4.28. A slight negative chondrite‐normalized Eu/Eu* (0.91) anomaly and significantly high PAAS‐normalized positive Eu/Eu* (1.39) values are consistent with derivation from a young undissected magmatic arc terrane. Tectonic discrimination diagrams suggest formation in an oceanic island arc to active margin/collision zone modelled to be located at the oceanic leading edge of Australia. Rapid uplift and erosion of the magmatic arc and older allochthonous blocks gave way to the rapid deposition of the Pandan Formation in the Late Cretaceous at the subequatorial region. Abstract : The Pandan Formation provides vital information on the Late Cretaceous evolution of Cebu Island in the Central Philippines. Collision of the proto‐Philippine arc with the East Philippine‐Daito arc modelled to be located at the oceanic leading edge of the Australian plate led to rapid uplift and erosion of the magmatic arc and continental derived sediments which gave way to deposition of the Pandan Formation in the Late Cretaceous at the subequatorial region.